Expenditures, investment and financing for sustainable development in Brazil - Young, Carlos E.F. (ECLAC SantiagoCL, 2002)
Examines the evolution and characteristics of the financing for the environment in Brazil, in order to identify the advances and retreats after the Rio 92 Conference.